Pengembangan Keterampilan Melalui Bimbingan Kerja pada Warga Binaan Pemasyarakatan di Lapas Narkotika IIB Purwokerto - Asda Octues; Nanda Aulia; Rafif Yumna Zaif; Yosi Hidayatul Fadillah; Kholil Lur Rochman (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
The high number of inmates in narcotics cases in Indonesia demands comprehensive coaching to support social reintegration. This study aims to describe the implementation of the job guidance program at the Class IIB Narcotics Prison in Purwokerto and its impact on the skill development of the inmates. Using an observational descriptive method, data was obtained through field observation, in-depth interviews, and literature studies for ± 40 days. The results of the study show that job guidance activities such as catfish cultivation, handicrafts, agriculture, ecoprint, and gastronomy make a significant contribution to improving practical skills, confidence, and work readiness of the inmates. These programs not only equip the inmates with technical skills, but also foster an entrepreneurial spirit and minimize the risk of recidivism. With a structured training approach, job guidance activities at the Class IIB Narcotics Prison in Purwokerto have proven to be an effective strategy in the process of rehabilitation and empowerment of inmates.